2014
DOI: 10.1590/1415-52732014000100001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weight and body composition changes on waist measurement of severely obese women receiving carbohydrate-restricted diet

Abstract: OBJECTIVE: To evaluate the effect of weight and body composition changes on waist measurement of severely obese women receiving a low-carbohydrate diet for a short-term. METHODS: Nineteen severely obese women divided into an intervention and a control group received a low-carbohydrate diet and a conventional diet, respectively, both with 1,200kcal, for seven days. Anthropometric measurements such as weight, body mass index, arm circumference, waist circumference (at the navel), two proposed measurements of wai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…However, Tayyem et al 2019 found that subjects with the highest visceral fat had a higher carbohydrate intake than subjects with the lowest visceral fat 30 . Similar results were also shown in another study where a low-carbohydrate diet intervention in obese female subjects resulted in a more significant reduction in waist circumference than the control group 41 .…”
Section: Issue 2sp (December 2023) 39-46supporting
confidence: 86%
See 1 more Smart Citation
“…However, Tayyem et al 2019 found that subjects with the highest visceral fat had a higher carbohydrate intake than subjects with the lowest visceral fat 30 . Similar results were also shown in another study where a low-carbohydrate diet intervention in obese female subjects resulted in a more significant reduction in waist circumference than the control group 41 .…”
Section: Issue 2sp (December 2023) 39-46supporting
confidence: 86%
“…In contrast, vegetable protein decreased waist circumference in men and women 39 . [39][40][41][42][43][44][45][46] Carbohydrate intake between the two groups did not show a significant difference during the intervention, although the treatment group showed lower results. A study found that carbohydrate intake is not associated with visceral fat changes 40 .…”
Section: Issue 2sp (December 2023) 39-46mentioning
confidence: 79%
“…Interestingly, low HDLc in obesity and MetSyn was associated with high carbohydrate diets, including refined grains, rather than high-fat diets in Korea [42,43]. Low carbohydrate diets significantly reduced Wt, WC, and fat %; however, the types of carbohydrate, refined/ unrefined grains, were a more important factor in increasing obesity than the total amount of carbohydrates [44,45]. Hypertensive patients with a high risk of MetSyn and CVD and individuals with obesity with high BMI & WC ate foods high in carbohydrates and cholesterol [46,47].…”
Section: Discussionmentioning
confidence: 97%
“…It is important to emphasize the importance of additional measures that can help monitor shape and weight gain, reflecting body composition, as shown in other studies in the relevant literature, such as body adiposity index (33) . Another point to be highlighted is the concern in connection with shape, weight and clinical implications; these are aspects; which have been studied by our research group (34)(35)(36)(37) .…”
Section: Discussionmentioning
confidence: 99%